"But how do you show that in a film?" Absence, Cartographic Anxiety, and Geographic Realism through the Landscapes of Akira Kurosawa's Dersu Uzala. Issue 1 (2nd January 2018) - Sharp, Laura
Abstract : In the last decade, postphenomenological landscape studies and cultural geographies of absence have brushed sides long enough for us to consider the roles of presence and absence in our understanding of landscape and our relation to it. This article extends these insights to the landscapes of cinema, drawing parallels between absence and the cartographic anxiety innate to both cinema and the geographic tradition. In so doing, this article shows how absence and the anxiety of loss inform our understanding of and emotional desire for geographic realism. To illustrate this point, the article analyzes the 1975 Academy Award–winning film, Dersu Uzala, directed by Japanese filmmaker Akira Kurosawa, as well as the conditions of the film's production. Through the film's diegesis and formal construction, we see that the performative act of conjuring the absent other through technological representations is an act that iteratively constitutes anew the self–other relation that is lost.